Práticas ESG de sustentabilidade ambiental na cidade de São Paulo - Penha, Thaluana Alves da (2023)
The research has the scope of analyzing, specifically, under the approach of the precepts of the ESG practice, a strand directed to the practice of environmental sustainability in the city of São Paulo. This movement is also in line with the 2030 Agenda of the United Nations (UN), which brings 17 Sustainable Development Goals (SDGs), aimed at 169 goals, to be achieved by the end of this decade. It foresees intense participation of public and private power working in synergy in the search for a more just, sustainable and solidary world. The study of the subject is justified by the fact that São Paulo is known as the economic heart of the largest economy in South America, with 12.4 million inhabitants, the most populous city in the southern hemisphere, the 14th largest city in the world in terms of population. In this context, today Public-Private Partnerships – PPPs prove to be an important tool for economic viability for the creation of infrastructure in the country, to the extent that, through the combination of efforts between the public and private areas, they can strengthen benefits in the scope of environmental management and sustainable development. The partnership proves to be an opportunity for the private sector, where national and transnational companies can increase their field of action, to satisfy public interests, even if aiming at profit. Finally, so that these positive results can be achieved, it has also become essential to gather a study on the performance of the Municipal Court of Auditors, as it has been demonstrated that the role of this body is to exercise, through the respective technical bodies, the external control of the contractual relations of the public administration with companies that fully acquire, among other requirements, the environmental legislation.